2020
DOI: 10.1111/are.14741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on the growth performance, physiological response and intestinal microbiota of juvenile Echiura worms ( Urechis unicinctus )

Abstract: Aquaculture of the Echiura worm Urechis unicinctus has developed rapidly in recent years. However, the artificial cultivation technology remains to be perfected. In this study, the effects of stocking density on the growth performance, physiological responses and intestinal microbiota of U. unicinctus juveniles were evaluated. Juvenile worms were randomly stocked at densities of 200 U (U. unicinctus/m3), 500 U, 1,000 U and 2,000 U, in aquariums. The results indicated that the contents of triglycerides, glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…The trend was similar with the previous feeding trial report of U. unicinctus juveniles with different salinities (Zheng et al, 2006;Li et al, 2019;Sun et al, 2020). In addition, the survival rate (93.33%), weight gain rate, and specific growth rate of U. unicinctus juveniles in this study were higher than the previous reports with survival rates from 65.37% to 82.67% at 30‰ salinity (Chen et al, 2020;Chen et al, 2021) which may result from the different diet of the feeding trial. The diet in this study was composed of Spirulina and Saccharomyces cerevisiae which was more suitable for U. unicinctus juvenile growth than the diet of sea mud and powders of Sargassum, Mytilusedulis, and Spirulina in the previous report (Chen et al, 2020;Chen et al, 2021).…”
Section: Effects Of Salinity On Growth Performancecontrasting
confidence: 86%
See 1 more Smart Citation
“…The trend was similar with the previous feeding trial report of U. unicinctus juveniles with different salinities (Zheng et al, 2006;Li et al, 2019;Sun et al, 2020). In addition, the survival rate (93.33%), weight gain rate, and specific growth rate of U. unicinctus juveniles in this study were higher than the previous reports with survival rates from 65.37% to 82.67% at 30‰ salinity (Chen et al, 2020;Chen et al, 2021) which may result from the different diet of the feeding trial. The diet in this study was composed of Spirulina and Saccharomyces cerevisiae which was more suitable for U. unicinctus juvenile growth than the diet of sea mud and powders of Sargassum, Mytilusedulis, and Spirulina in the previous report (Chen et al, 2020;Chen et al, 2021).…”
Section: Effects Of Salinity On Growth Performancecontrasting
confidence: 86%
“…To investigate the variation of intestinal microbial composition under salinity stress at the genus level more comprehensively, the unclassified genus was also analyzed in this study. Similar methods have been used in microbial composition analysis (Chen et al, 2020). The results indicated that the dominant genera of U. unicinctus intestinal microbiota from the 10‰ group were unidentified Legionellaceae (89.67%) and Labrenzia (3.95%); 15‰ and 20‰ groups with Labrenzia (35.93% and 25.77%), unidentified Legionellaceae (25.67% and 7.00%) and unidentified Rhodobacteraceae (7.67% and 10.97%); 30‰ group with Vibrio (50.59%), Shimia (8.98%), and unidentified Rhodobacteraceae (7.33%), whereas in the 40‰ group, the dominant genera were unidentified Rhodobacteraceae (41.33%), Vibrio (11.62%) and Labrenzia (7.73%) (Figure 5).…”
Section: Effects Of Salinity On Intestinal Microbiota Compositionmentioning
confidence: 99%
“…However, prolonged elevation of Cor levels can cause serious cell damage [83]. La is also a crucial biomarker for stress response in aquatic animals [84]. For the juvenile flounder (Paralichthys orbignyanus) raised in tanks, the serum Cor was significantly increased at high stocking density (7.8 kg/m 3 , 15 d) [85].…”
Section: Effect Of Stocking Density On Stress Responsementioning
confidence: 99%
“…These results indicated that culture method had an obvious effect on the composition of the intestinal microbiota in U. unicinctus. We previously showed that the stocking density and bottom substrate also had significant effects on the intestinal microbiota of U. unicinctus (Chen et al, 2020(Chen et al, , 2021. The intestinal microbiota has been referred to as the 'second genome' of animals, and it is responsible for regulating many biological functions of the host, including the digestion and absorption of nutrients, as well as the immune responses to external stress (Wikoff et al, 2009).…”
Section: Figure 4amentioning
confidence: 99%